Analysis Of Risk Profile, Good Corporate Governance, Earnings, Capital On Potential Financial Distress - Putri, Chintya (Fakultas Ekonomi dan Bisnis dan LPPM Universitas Negeri Jakarta, 2024)
Banks are financial organizations that are regularly subject to strict regulations and standards set by the Financial Services Authority (OJK) in order to maintain business continuity and stakeholder and public trust. RGEC (Risk Profile, Good Corporate Governance, Earnings, Capital) analysis is a crucial method for assessing a bank's compliance with OJK criteria and monitoring its financial health and stability. This study uses RGEC and a quantitative descriptive technique based on the officially issued financial statements to examine the financial statements of PT Bank Rakyat Indonesia from 2019 to 2023. With a Composite Rating of 1 (PK-1) in the